Relationships of Mother's Knowledge and Attitudes with Hepatitis B Immunization Practices (H1) in Working Area of Mangkang Health Center in Semarang - Ramelan Sugijana; Purnomo Purnomo; Wien Soelistyo Adi (UPPM Poltekkes Kemenkes Semarang, 2015)
Immunization is one way to improve one's immunity to be active and able to prevent certain diseases, such as hepatitis B immunization zero to prevent hepatitis. Healthy Indonesia 2010 is targeting that 80 % of babies in the whole village/ villages in Indonesia have received hepatitis B immunization. Hepatitis B immunization coverage at Mangkang Health Center in 2010 was 83.53 %. However, hepatitis B immunization coverage (H1) in Semarang City in 2010 was 23.03 %, and the figure is still far from the target set by the Healthy Indonesia 2010. This study was conducted to describe the relationships of mother's knowledge and attitudes with hepatitis B immunization practices (H1) in Mangunharjo Village, Mangkang Health Center. The benefit of this research can be regarded as a source of information for researchers, health professionals, educational institutions, and the public about the importance of immunization with hepatitis B (H1) in infants. The presented study was a descriptive study, using a questionnaire for data collection. The population of this study is all mothers of infants aged 8 days to 6 months in Mangunharjo Village. Sampling method was used to recruit a sample of 50 mothers. The variables were levels of knowledge and attitudes of mothers on immunization hepatitis B (H1) for the baby. The results showed that most mothers had a secondary education level. The level of knowledge of mothers on immunization hepatitis B (H1) in Mangunharjo Village was high, which meant that the majority of mothers knew about immunization program of Hepatitis B (H1). The mother's attitudes in hepatitis B immunization (H1)for infants and for babies in the village were also very positive. Chi Square test found an association of maternal attitudes and practices of immunization of Hepatitis B (H1) (p value < 0.05).